A Study of the Cyclicity Indicators of the Country's Economic Development. Issue 5 (4th May 2017) - Tiapkina, M.F.; Mongush, I.D.; Akimova, I.O.
Abstract : This article analyzes the main indicators of Russia's economic development (gross domestic product, unemployment rate, consumer price index, fixed investment, and the growth rate of industrial production) in 2000–2013. Such indicators make it possible to construct economic cycles. In addition, this article provides a polynomial forecast for 2014–2015 with respect to the medium-term cycles in the country's economic development. This forecast does not take into account the government's anticyclical policy.